The Level of Acquisition Pertaining to Concepts of Knowledge Economy Among Physical Education Supervisors in Al-Karak Directorate of Education - Al-Qralleh, Amani M.; Mismar, Bassam A.; Matarneh, Mohammad (Dirasat: Educational Sciences, 2020)
The purpose of this study is to investigate the level of acqusition regarding knowledge economy concept amongest the physical education supervisors in Al-Karak directorate of education, and their concepts of knowledge economy regarding study's demographic variables such as (sex, experience, and scientific qualification). The researchers used descriptive method due to its suitability of the study. The sample of the study was (15) physical education supervisors from Al-Karak directorate of education. The questionnaire was designed for the purpose of the study. It contained (33) items distributed into five dimensions, the scientific coofficients such as content validity and reliability was checked out.data were collected and treated by using descriptive statistics and MANOVA. The results showed that the level of acquisition among the physical education supervisors in Al-Karak directorate for the concepts of knowledge economy was relatively moderate in all dimentions. Moreover, the results showed that there were no statistically significant differences among the physical education supervisors for concepts of knowledge economy according to the variables (sex, experience, and scientific qualification). The researchers recommended that the need to activate the concepts of knowledge economy in the diroctrates of education in city of Alkarak by encouraging and reinforcing the proper supervisory behaviors..